2012
DOI: 10.1111/j.1526-4637.2012.01382.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an Acute Pain Service on Pain Outcomes with Combat-Injured Soldiers at Camp Bastion, Afghanistan

Abstract: Findings from this quality of pain care study show that aggressive multimodal analgesia interventions by an APS in a CSH is associated with decreased pain intensity and increased pain relief.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(10 citation statements)
references
References 22 publications
(20 reference statements)
0
8
0
2
Order By: Relevance
“…For example, Buckenmaier et al. () and Buckenmaier, Mahoney, Anton, Kwon, and Polomano () found that incorporating aggressive multimodal regional analgesia after injury significantly reduced pain intensity in combat‐injured soldiers compared to soldiers receiving standard pain management. Clinical characteristics of injury (e.g., severity and mechanism) are associated with the risk of developing postinjury PTSD and depression (Grieger et al., ), as well as acute and chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Buckenmaier et al. () and Buckenmaier, Mahoney, Anton, Kwon, and Polomano () found that incorporating aggressive multimodal regional analgesia after injury significantly reduced pain intensity in combat‐injured soldiers compared to soldiers receiving standard pain management. Clinical characteristics of injury (e.g., severity and mechanism) are associated with the risk of developing postinjury PTSD and depression (Grieger et al., ), as well as acute and chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…In the trauma specifically, Buckenmaier et al have published extensively on the application and benefits of regional anesthesia and aggressive acute pain management in the wounded soldier [10,24,28,[32][33][34][35][36]. The work of their group has clearly demonstrated outcomes benefit of regional anesthesia as a component of multimodal analgesia in improving the pain control of wounded soldiers [28].…”
Section: Physiological and Psychological Consequences Of Acute Painmentioning
confidence: 98%
“…In the trauma specifically, Buckenmaier et al have published extensively on the application and benefits of regional anesthesia and aggressive acute pain management in the wounded soldier [10,24,28,[32][33][34][35][36]. The work of their group has clearly demonstrated outcomes benefit of regional anesthesia as a component of multimodal analgesia in improving the pain control of wounded soldiers [28]. In addition to improved pain control, the early and successful control of pain may be associated with improvement in the psychological consequences of trauma such as anxiety, chronic pain, and potentially long-term psychological distress [2,3,7,12,13,15,[23][24][25][26][27][28][29][30][31]34].…”
Section: Physiological and Psychological Consequences Of Acute Painmentioning
confidence: 99%
“…18 Interventional analgesia, as part of an acute pain management service trialed in Afghanistan, used trigger point injections, as well as the use of regional nerve blocks and epidural analgesia, as a means to decrease pain intensity, to provide increased pain relief, and to avoid the adverse effects associated with opioid therapy. 19 This may prove particularly beneficial in the management of postamputation pain, where phantom limb sensations were more effectively treated with early regional blockade. 20 Continuous peripheral nerve blocks, including placement of continuous transversus abdominis plane catheters, demonstrated that advanced regional anesthesia could be accomplished in a forward deployed environment.…”
Section: Anesthetic As Analgesic Therapy: Ketaminementioning
confidence: 99%